Dose Analysis in Boron Neutron Capture Therapy on Prostate Cancer using PHITS Program Version 3.32 - Fernando, Rio Agustian Gilang; Dwijananti, Pratiwi; Masturi, Masturi; Sunarno, Sunarno; Sardjono, Yohannes (Universitas Negeri Semarang, 2025)
Prostate cancer is the second most common cancer in male worldwide. Boron Neutron Capture Therapy (BNCT) offers cancer treatment with minimum side effects. BNCT is radiation therapy that uses the 10B isotope and neutron beams which can selectively destroy tumor cells. The resulting radiation dose cannot be measured directly, so a computational method is needed to calculate the dose. The aim of this research is to determine the effective boron concentration, determine the optimal direction of irradiation, and determine the duration of irradiation time at an effective boron concentration for BNCT of prostate cancer. The computational method used is the Monte Carlo method with PHITS Version 3.32 software. The phantom used is an adult male ORNL phantom. The type of prostate cancer modeled is adenocarcinoma with an intermediate risk group. The neutron source is a 30 MeV cyclotron. Variations in 10B concentrations used were 100, 110, 120, 130, 140, and 150 µg/g boron/cancer tissue. The variations in direction used are: anterior-posterior, lateral-anterior oblique, and left-lateral. This study yield that the effective boron concentration used for BNCT in prostate cancer is 150 µg/g boron/cancer tissue. The most optimal radiation direction for BNCT of prostate cancer is the anterior-posterior direction. The duration of irradiation time required for a boron concentration of 150 µg/g boron/cancer tissue is 1 hour 16 minutes 10 seconds.